POTENSI JUS TOMAT MENURUNKAN KADAR GULA DARAH SEWAKTU (GDS) PADA PASIEN DIABETES MILITUS - sudiarto sudiarto; widi rusmono (Poltekkes Kemenkes Kalimantan Timur, 2018)
Diabetes mellitus (DM) is a disease of excess blood sugar levels in the body resulting in increased blood sugar levels due to lack of insulin. Long-term hyperglycemia may contribute to chronic microvascular complications (kidney and eye disease) and neuropathic complications (nerve disease). The type of research is quasy-experiment with pretest-posttest control group design. The research sample was diabetic militus with blood sugar level> 200mg / dl at Banjarnegara Islamic Hospital was taken using simple random sampling. The intervention group received 300 ml tomato juice twice morning and evening for three days. 200 ml tomato juice made from 180 grams of tomatoes. The control group did not get tomato juice. Both groups received 2 x 5 mg glibenclamide therapy. The analysis used was Wilcoxon and Mann-Whitney. The results showed a decrease in mean blood glucose levels (GDS) in the intervention group versus the control group. The result of statistical analysis p value <0,05 mean there is a significant decrease of blood glucose level (GDS) of intervention group and p value> 0,05 means no significant decrease of blood glucose level during control group (GDS). The statistical results of Unpaired t-test for comparison between two groups obtained blood glucose level (GDS) of p value <0.05 which means significant decrease of blood glucose level (GDS). Data analysis showed significant results so that tomato juice can be an alternative choice in decreasing blood sugar levels (GDS) in diabetics militus.